Perceptions of dental professionals on the use of silver diamine fluoride with or without light-curing - Win Myat Phyo; Palinee Detsomboonrat (BMC Oral Health)
Abstract Background According to anecdotal reports, SDF’s ability to arrest caries can be enhanced by light-curing in a clinical setting. The purpose of the present study was to explore the dental professionals’ perceptions of using SDF and to understand the barriers and enabling factors to using SDF with and without light-curing. Methods A qualitative study was conducted with dental professionals who had experience with using SDF with and without light-curing. A purposive heterogeneous and convenience sampling approach was applied to ensure the inclusion of participants with different employment and experience levels. Eighteen participants (dental students (undergraduate and postgraduate), dental personnel (practicing dentists and dental hygienists), and academics) with ages ranging from 22 to 53 years old participated in the study. The data were collected through a semi-structured open-ended questionnaire. Manual line-by-line coding and content analysis methods were used for data analysis. Results Most participants indicated a preference for light-curing, citing perceived benefits, such as quicker treatment, convenience, better visibility, prevention of saliva contamination, and ensuring thorough SDF coverage. However, some participants voiced concerns, based either on existing practice guidelines or due to insufficient evidence regarding the efficacy of light-curing. Additionally, one participant proposed a hybrid approach based on tooth location, suggesting avoiding using light-curing on anterior teeth, while utilizing it on posterior teeth. Conclusion The participants’ responses indicated that the use of SDF with and without light-curing each has its merits. Using SDF with light-curing emerged as the preferred method due to perceived benefits. e.g., quicker treatment, better moisture control. However, concerns regarding existing guidelines and the lack of robust evidence for its efficacy were also identified. This study highlights the need for additional research to address the knowledge gaps and provide stronger evidence to support the use of light-curing after SDF application.